Defending the Swamp Dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2026)
"Drake and his friend Obi meet a new Dragon Master, Kinti, and venture into the swamp to help save the Swamp Dragon, who has been mistaken for a terrifying monster"-- Provided by publisher.